Effect of 4% titanium tetrafluoride solution on dental erosion by a soft drink: An in situ/ex vivo study - Magalhaes, Ana Carolina [UNESP]; Rios, Daniela; Honorio, Heitor Marques; Jorge, Alberto Moreira; Delbem, Alberto Carlos Botazzo [UNESP]; Buzalaf, Marilia Afonso Rabelo (Pergamon-Elsevier B.V. Ltd, 2008)
Objective: This in situ/ex vivo study assessed the effect of titanium tetrafluoride (TiF4) on permanent human enamel subjected to erosion.Design: Ten volunteers took part in this study performed in two phases. In the first phase (ERO), they wore acrylic palatal appliances containing two enamel blocks, divided into two rows: TiF4 (F) and no-TiF4 (no-F). During the 1st day, the formation of a salivary pellicle was allowed. In the 2nd day, the TiF4 solution was applied on one row (ERO + F), whereas on the other row no treatment was performed (ERO + no-F). From 3rd until 7th day, the blocks were subjected to erosion, 4x per day. In the 2nd phase (no-ERO), the volunteers wore acrylic palatal appliances containing one enamel block, during 2 days, to assess the effect of TiF4 only (no-ERO + F). Enamel alterations were determined using profilometry (wear), microhardness (%SMHC) tests, scanning electron microscope and microprobe analysis. The %SMHC and wear were tested using ANOVA and Tukey's post hoc tests (p < 0.05).Results: The mean of %SMHC and wear ( mu m) values ( +/- S.D.) were, respectively: ERO + F -73.32 +/- 5.16(A)/2.40 +/- 0.60(a); ERO + no-F -83.49 +/- 4.59B/1.17 +/- 0.48(b) and no-ERO + F -67.92 +/- 6.16(A)/0.21:E 0.09(c). In microscope analysis, the no-F group showed enamel with honeycomb appearance. For F groups, it was observed a surface coating with microcracks. The microprobe analysis revealed the presence of the following elements (%) in groups ERO + F, ERO + no-F and no-ERO + F, respectively: Ca (69.9, 72.5, 66.25); P (25.9, 26.5, 26.06); Ti (3.0, 0, 5.93).Conclusions: The TiF4 was unable to reduce dental erosion. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: erosion; soft drinks; fluoride; titanium